Internalisasi nilai multikultural berbasis kearifan lokal: Osing dalam kurikulum muatan lokal di sekolah dasar Kabupaten Banyuwangi - Lutfi Sholiha, Anta Kuna (Maliki Interdisciplinary Journal, 2026)
This study aims to conduct a comprehensive analysis of the mechanisms and processes, in order to implement values ​​that are directly applied through the local curriculum based on the wisdom of the Osing Community at the Elementary School level in Banyuwangi Regency. The Osing tribe has high socio-cultural values. In the increasingly modern era, of course, the flow of digitalization is increasingly dominant, the impact of this infiltration of transnational culture has the potential to erode local identity. Through data collected from participant observation techniques, as well as analysis of several local content curriculum modules. It can be revealed that the process of internalizing multicultural values ​​is carried out through three interconnected stages, including: first, the transformation of values ​​in the form of cognitive recognition of symbols and cultural philosophy, second, the formation of values ​​through interactive dialogue and dialectics between teachers and students, third, the habitualization of students' daily behavior applying local wisdom values ​​such as collectivity and tolerance. This shows that Osing local wisdom not only functions as an effort to preserve local wisdom, but also grounds the values ​​of Pancasila. The application of Osing local wisdom to the elementary school curriculum can enhance students' cultural intelligence, minimize bullying, and foster a sense of pride in their regional identity. This study concludes that internalizing locally based multicultural values ​​is effective in maintaining national integration and social cohesion from an early age.